Cargo flow and transit impacts on port development - Paulauskas, Vytautas; Lukauskas, Valdas (Transport, 2003)
The article analyses the changes of cargo flow structures, the distribution by overseas regions and their potential impact on port development. The analysis on how the cargo type and transit regions influence on the vessel capacity has been carried out. A view on the general range of ship size employed on the Baltic is given. The potential of the Klaipeda seaport is approached in respect of certain cargo flow evaluation. The tendencies of changing the main cargo flows through the Klaipeda seaport and the way they influence on ship sizes are researched. Possible influence of large-sized ship traffic on the port operations and development has been considered. First Published Online: 19 Dec 2011